Violence risk assessment for females: the HCR-20 - Rossdale, Sapphire-Violet (2019)
Violence in females has received little empirical attention, compared to males. However, contemporary society has seen an increase in female violence, as well as offences committed by females, generally. Therefore, gaining further insight female violence is important for understanding, measuring, preventing and rehabilitating females. This thesis includes chapters which apply a meta analytical approach to the existing research for the HCR-20.